APPLYING LANGUAGE LEARNING STRATEGY INSTRUCTION TO IMPROVE THE STUDENTS’ READING COMPREHENSION ABILITY - Afdaleni Afdaleni (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
There are some factors that may influence the students’ success in their reading comprehension. One of them is applying language learning strategy instruction toward the students in their reading comprehension activity in order that they can improve their reading comprehension ability. As has been known that students use learning strategies to help them understand information and solve problems in their reading comprehension. Students who do not know or use good and appropriate language learning strategies in their reading comprehension often learn passively and even they get failure at their school. Language Learning Strategy instruction focuses on making students more active learners by teaching them how to learn and how to use what they have learned to be successful learners. This article is about Applying Language Learning Strategy Instruction to improve the learners’ Reading Comprehension Ability. It is expected that this article can become useful information for the teachers, learners and readers who concern with the reading comprehension in general.